2017
DOI: 10.1038/srep40311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal-mediated aerosol-phase oxidation on secondary organic aerosol formation from the ozonolysis and OH-oxidation of α-pinene

Abstract: The organic component is the most abundant fraction of atmospheric submicron particles, while the formation mechanisms of secondary organic aerosol (SOA) are not fully understood. The effects of sulfate seed aerosols on SOA formation were investigated with a series of experiments carried out using a 9 m3 smog chamber. The presence of FeSO4 or Fe2(SO4)3 seed aerosols decreased SOA yields and increased oxidation levels in both ozonolysis and OH-oxidation of α-pinene compared to that in the presence of ZnSO4 or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…The degree of oxidation is a parameter of interest for organic aerosol, as atmospheric photochemical aging occurs over an aerosol’s lifetime, yielding more oxidized species and aerosol with a higher 65 . The observed difference in ROS/RNS levels between AS and FS seeded SOA is likely an effect of the degree of oxidation, where the presence of iron serves to increase the oxidation of species via Fenton-like reactions (Table S1 ) 51 , 52 . In fact, a positive exponentially decreasing trend was observed between ROS/RNS levels and of aerosol for all experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of oxidation is a parameter of interest for organic aerosol, as atmospheric photochemical aging occurs over an aerosol’s lifetime, yielding more oxidized species and aerosol with a higher 65 . The observed difference in ROS/RNS levels between AS and FS seeded SOA is likely an effect of the degree of oxidation, where the presence of iron serves to increase the oxidation of species via Fenton-like reactions (Table S1 ) 51 , 52 . In fact, a positive exponentially decreasing trend was observed between ROS/RNS levels and of aerosol for all experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After gas species and seed particles in the chamber were mixed well, the photooxidation experiment was carried out with the fan turned off. In this work, the OH concentrations in the chamber were (1.3-2.2) × 10 6 molecules cm −3 , calculated based on the degradation rate (7.53×10 −11 cm 3 molecule −1 s −1 ) of guaiacol with OH radicals (Coeur-Tourneur et al, 2010a). The chemicals and gas samples used in this work were described in Supplement.…”
Section: Methodsmentioning
confidence: 99%
“…Its emission factor of wood burning is in the range of 172-279 mg kg −1 wood . In recent years, the reactivity of gas-phase guaiacol toward OH radicals (Coeur-Tourneur et al, 2010a), NO 3 radicals (Lauraguais et al, 2016;Yang et al, 2016), Cl atoms (Lauraguais et al, 2014a), and O 3 (El Zein et al, 2015) has been investigated, suggesting that its degradation by OH and NO 3 radicals might be predominant in the atmosphere. Meanwhile, several studies have reported the significant secondary organic aerosol (SOA) formation from guaiacol oxidation by OH radicals, produced from the photolysis of the OH precursors (i.e., H 2 O 2 and CH 3 ONO) (Ahmad et al, 2017;Lauraguais et al, 2014b;Yee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies concentrated on the SOA production from the oxidation of volatile organic compounds (VOCs), the reported SOA yields showed high variability for a given precursor (Chu et al, 2016(Chu et al, , 2017Ge et al, 2017a;Lauraguais et al, 2012Lauraguais et al, , 2014bNg et al, 2007;Sarrafzadeh et al, 2016;Yee et al, 2013). This variability is mainly dependent on the numerous factors, e.g., pre-existing seed particles, SO2 level, NOx level, humidity, and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This variability is mainly dependent on the numerous factors, e.g., pre-existing seed particles, SO2 level, NOx level, humidity, and temperature. Two of the critical factors are the impacts of preexisting seed particles and SO2 level on SOA formation (Chu et al, 2016(Chu et al, , 2017Ge et al, 2017a). In addition, the atmospheric concentration of SO2 could be up to close 200 ppb in the severely polluted atmosphere in China, and SOA from biomass burning and sulfate formation could significantly contribute to severe haze pollution (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%